Peningkatan Kemampuan Siswa Menulis Teks Berbentuk Procedure Melalui Pembelajaran Make A Match - Dasma Manurung (JURNAL GLOBAL EDUKASI, 2021)
Abstract: This classroom action research was conducted in Class IX A of SMP Negeri 2 Uluan, kab. Toba with 41 students. The objectives to be achieved in this study are to improve students' ability to compose procedure texts, develop learning strategies and learning models that are effective, efficient and fun. Students can be actively involved in communication activities by expressing their ideas, opinions and feelings in a simple way, both verbally and in writing. This study uses a classroom action research method by applying the match a make learning model. The results of the observation that 29 of 41 students (70.73%) were seen to be active in the learning process. Only 1 student (0.22%) scored the result of the written test evaluation who had not yet reached the KKM. The post test scores of students in the form of individual evaluations through Student Worksheets showed as many as 3 students (0.07%) got a 'good' C score, 17 students (0.41%) got a 'fair' D score, 20 students (0.49%) got an E 'poor' Keywords: make a match; write text; procedure Abstrak: Penelitian tindakan kelas ini dilaksanakan di Kelas IX A SMP Negeri 2 Uluan, kab. Toba dengan jumlah siswa 41 orang. Adapun tujuan yang ingin dicapai dalam penelitian ini adalah meningkatkan kemampuan siswa untuk menyusun teks procedure, mengembangkan strategi pembelajaran dan model pembelajaran yang efektif, efisien dan menyenangkan. Siswa dapat melibatkan diri secara aktif dalam kegiatan komunikasi dengan mengemukakan gagasan, pendapat dan perasaannya secara sederhana baik lisan maupun tertulis. Penelitian ini menggunakan metode penelitian tindakan kelas dengan menerapkan model pembelajaran match a make. Hasil pengamatan bahwa 29 dari 41 siswa (70,73%) terlihat aktif dalam proses pembelajaran. Nilai siswa hasil dari evaluasi test tulis hanya 1 orang siswa (0,22%) saja yang masih belum mencapai KKM. Nilai post test siswa berupa evaluasi individu melalui Lembar Kerja Siswa menunjukkan sebanyak 3 siswa (0,07%) mendapat nilai C ‘good’, 17 siswa (0,41%) mendapat nilai D ‘fair’, 20 siswa (0,49%) mendapat nilai E ‘poor’ Kata kunci: make a match; menulis teks; procedure